Antioxidants for health management / Fatimah Salim, Nor Syarmila Shuib and Raihana Mohd Yusof - Salim, Fatimah; Shuib, Nor Syarmila; Mohd Yusof, Raihana (Universiti Teknologi MARA, Perlis, 2022)
Antioxidants are technically reductant molecules that prevent the oxidation of other molecules. As other living systems, human biological molecules are also prone to oxidation reactions. In order to repair all of the oxidation damage, human body is naturally producing antioxidants or known as endogenous antioxidant. Unfortunately, the body’s production of antioxidants declines with age and this is found to be a strong factor in contributing to premature aging and degenerative diseases. Researchers have found that exogenous antioxidants which are obtained from foods may work together with endogenous antioxidants to maintain the redox reaction balance in the body. There are thought to be hundreds and possibly thousands of substances that can act as exogenous antioxidants including carotenoids, flavonoids, indoles, polyphenols, essential vitamins (A, C, E), and the minerals copper, zinc, manganese, and selenium. Thus, this paper intended to give insights on the endogenous and exogenous antioxidants, supplements as antioxidant, as well as guiding readers to get benefits of antioxidants from foods for a better health management. It was found that diet containing fruits and vegetables link to superior overall health effects. However, fruits and vegetables should be consumed regularly by considering the right cooking method to get the best effect due to the fact that some antioxidants are sensitive to some cooking method. Apart from diet containing high antioxidants, adopting active lifestyles with consistent exercise and stress management are also required to ensure good and long lasting health